2012
DOI: 10.1371/journal.pone.0044367
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione Depletion and Carbon Ion Radiation Potentiate Clustered DNA Lesions, Cell Death and Prevent Chromosomal Changes in Cancer Cells Progeny

Abstract: Poor local control and tumor escape are of major concern in head-and-neck cancers treated by conventional radiotherapy or hadrontherapy. Reduced glutathione (GSH) is suspected of playing an important role in mechanisms leading to radioresistance, and its depletion should enable oxidative stress insult, thereby modifying the nature of DNA lesions and the subsequent chromosomal changes that potentially lead to tumor escape.This study aimed to highlight the impact of a GSH-depletion strategy (dimethylfumarate, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 49 publications
1
35
0
Order By: Relevance
“…However, cancer cells also generate a large amount of intrinsic antioxidants such as GSH, superoxide dismutase and catalase to counteract ROS and tolerate ROS-induced oxidative stress, leading to altered redox balance 1,17 . In particular, a large amount of GSH is known to play a critical role in cellular redox maintenance and antioxidative systems 8,10 . We also found that DU145 cells have the highest level of GSH and H 2 O 2 and the least level of GSH and H 2 O 2 were observed with normal NIH3T3 cells † † † ** ** *** *** *** *** *** ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, cancer cells also generate a large amount of intrinsic antioxidants such as GSH, superoxide dismutase and catalase to counteract ROS and tolerate ROS-induced oxidative stress, leading to altered redox balance 1,17 . In particular, a large amount of GSH is known to play a critical role in cellular redox maintenance and antioxidative systems 8,10 . We also found that DU145 cells have the highest level of GSH and H 2 O 2 and the least level of GSH and H 2 O 2 were observed with normal NIH3T3 cells † † † ** ** *** *** *** *** *** ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Accumulating evidence has suggested that abnormal cancer cells are under oxidative stress associated with an increased production of ROS due to disrupted ROS homeostasis and cancer cells have also adapted to oxidative stress by activating antioxidant systems often through the upregulation of glutathione (GSH) 2,[7][8][9][10] . Ironically, cancer cells are also known to utilize ROS to drive proliferation and other events required for tumour development 11,12 .…”
mentioning
confidence: 99%
“…However, despite this induction of cell death, some tumor cells are capable of survival by undergoing endomitosis and reentering the cell cycle [23], and therefore can acquire a resistant phenotype [12,24]. However, as we have demonstrated that ceramide is an essential mediator in the course of late apoptosis activated during mitotic catastrophe, the modulation of this pathway will therefore be of interest in the future development of drugs in association with radiotherapy [25].…”
Section: Article In Pressmentioning
confidence: 96%
“…The limit of our study is to know the exact rate of TGFB1 from which the spermatozoa become highly altered and therefore utilizable for fertilization [18][19][20][21]57]. Therefore we recommended the evaluation of seminal status of TGFß1 before any attempt of assisted reproduction.…”
Section: Resultsmentioning
confidence: 99%
“…Subjects currently on any medication or antioxidant supplementation were not included [16][17][18][19][20][21][22][23][24]. In addition, subjects with testicular varicocele, genital infection, leukocytespermia, chronic illness and serious systemic diseases, smokers and alcoholic men were excluded from the study because of their well-known high seminal ROS levels and decreased antioxidant activity.…”
Section: Exclusion Criteriamentioning
confidence: 99%